Anthraquinone Emodin Inhibits Tumor Necrosis Factor Alpha-Induced Calcification of Human Aortic Valve Interstitial Cells via the NF-κB Pathway - Xu, Kang; Zhou, Tingwen; Huang, Yuming; Chi, Qingjia; Shi, Jiawei; Zhu, Peng; Dong, Nianguo (Frontiers in Pharmacology, 2018)
Exploring effective therapies for delaying calcific heart valve disease (CHVD) is the focus of current cardiovascular clinical and scientific research. In this study, human aortic valve interstitial cells (hVICs) were isolated from patients with CHVD. After expansion, cultured hVICs were induced with the tumor necrosis factor-alpha (TNF-α) with or without anthraquinone emodin (EMD) treatments. Cytotoxicity and flow cytometric analysis were used to assess cell growth, while Alizarin Red S staining was used to detect hVICs calcification. Furthermore, RNA-sequencing analysis was utilized to investigate changes in mRNA profiles of cells cultured in TNF-α conditioned medium with or without EMD. Western blotting and qRT-PCR analyses were used for the verification of key selected genes. Our results indicated that EMD had limited influence on hVIC morphology, whereas in a dose-dependent fashion, EMD interfered with hVIC growth under TNF-α conditioned cell culture. Additionally, hVICs treated with TNF-α plus EMD, presented a gradual decrease of positive Alizarin Red S staining, when compared with cells treated with TNF-α only. Notably, cells treated with TNF-α plus EMD showed 1874 differential expression genes (DEGs), among them, 1131 were upregulated and 743 were downregulated. These DEGs displayed an enrichment of biological functions and signaling pathways, among them, BMP2, RELA, TNF, and TRAF1, were found to be significantly suppressed by EMD and selected given their role in mediating hVIC calcification. In conclusion, our study shows that EMD inhibits TNF-α-induced calcification and phenotypical transformation of hVICs via the NF-κB signaling pathway, thereby preventing calcification events stimulated during acute inflammatory responses.